2017
DOI: 10.1016/j.jbusres.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Psychological ownership and music streaming consumption

Abstract: Streaming is becoming the most common format from which people access, share and listen to music and it is suggested that such practices are indicative of a shift towards a ‘post-ownership’ economy. In the case of music, consumers may place greater value (emotional and monetary) on the physical product because of the lack of legal ownership and/or absence of perceived ownership associated with streaming. This article examines how experiences of ownership are articulated through music streaming formats via qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
155
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(186 citation statements)
references
References 29 publications
6
155
0
10
Order By: Relevance
“…Scholars in marketing and consumer research observed a general shift from the ownership to the access model and suggested digital media content as examples of or candidates for communal sharing and short-term access in the "post-ownership economy" (Belk, 2014(Belk, , p. 1599 or "the age of access" (Rifkin, 2000, p. 1). Although Watkins et al (2016) opposed the use of the ownership and access dichotomy, many scholars/observers have used this dichotomy to suggest that consumers are moving away from ownership to access-based consumption (Belk, 2014;Lawson, Gleim, Perren, & Hwang, 2016;Rifkin, 2014;Rowley, 2008;Sinclair & Tinson, 2017). An example of this shift is the proliferation of the access-based digital services model, including subscription services for e-books, digital music, and digital videos.…”
Section: Ownership Vs Accessmentioning
confidence: 99%
“…Scholars in marketing and consumer research observed a general shift from the ownership to the access model and suggested digital media content as examples of or candidates for communal sharing and short-term access in the "post-ownership economy" (Belk, 2014(Belk, , p. 1599 or "the age of access" (Rifkin, 2000, p. 1). Although Watkins et al (2016) opposed the use of the ownership and access dichotomy, many scholars/observers have used this dichotomy to suggest that consumers are moving away from ownership to access-based consumption (Belk, 2014;Lawson, Gleim, Perren, & Hwang, 2016;Rifkin, 2014;Rowley, 2008;Sinclair & Tinson, 2017). An example of this shift is the proliferation of the access-based digital services model, including subscription services for e-books, digital music, and digital videos.…”
Section: Ownership Vs Accessmentioning
confidence: 99%
“…The way consumers listen to music has also changed, mainly through access made easier in the internet through digital spaces and streaming platforms like iTunes or Spotify (Sinclair and Tinson, 2017). Nowadays, consumers face "a myriad of music platforms with widely different characteristics in terms of business model (advertising supported, fee-based, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Through new concepts of digital music distribution (Doerr et al, 2010) such as music as a service (MaaS), fans everywhere can now listen to every song of every band over the internet as a service, blurring national boundaries. Digital music came to stay, accounting for the first time for over 50% (54%) of total industry revenues , while conversely physical product sales are declining (Sinclair and Tinson, 2017) together with illegal downloading (Sinclair and Green, 2016). In particular, licensed music streaming services (MSS) overcame $17.3 billion of sales in 2017, following a 41.1% sharp growth , and are expected to reach a total of 978 million users and 220 million subscribers by 2020 (Statista, 2018b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations